Economic Diversification and Government Sustainable Supply Chain Governance: An Empirical Approach on Government Expenditure of Iraq - Mohammed Dhannoon Mohammed; Hassnain Raghib Talab; Oday Salim Ali (International Journal of Supply Chain Management, 2018)
This paper examines and analyses evidence pertaining to economic diversification and government sustainable supply chain governance in the Iraqi government expenditure from 2004 to 2016. The purpose of the paper is to test to what extent the government has recognized the importance of economic diversification and government sustainable supply chain governance in the process of growth of government revenue and hence what are the measures adopted aiming at improving government revenue. Based on evidence, the paper goes on to identify the determinants of economic diversification and governance in the Iraq. This paper uses recent growth theories and statistical techniques to empirically test for the association between economic diversification (gross domestic product (GDP), importation, exportation and total fixed capital formation), governance (political stability, quality regulation, effective government, control of corruption, rule of law and accountability) and government expenditure. Results obtained from data analysis indicate a strong relationship between economic diversification and government expenditure. However, the relationship between Iraqi governance and government expenditure revealed a significant relationship which shows that increase in the budget for effective governance did not apparently lead to quality improvement in the government expenditure. Iraq as part of the countries under the Gulf Cooperation Council (GCC) shares specific structural economic features. The country depends heavily on the hydrocarbon sector despite the huge accumulated financial surplus and the governments investment on the economy; outcomes have fallen short of targets set out for the national visions, while the challenges of economic diversification and governance continue. The overarching focus will be on the challenges of diversification in terms of strategic planning, policy-making, implementation, and global best practices. This study revealed that to achieve these goals, the government in the whole world needs to improve and maintain the government expenditure by diversifying into the economic gross domestic product (GDP), importation, exportation and total fixed capital formation.